Environmental factors associated with developmental coordination disorder in preschool children in urban area of Suzhou city - Hua, Jing (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2014)
OBJECTIVE: A population-based study on developmental coordination disorder (DCD) was conducted in Suzhou to explore the impacts of family and kindergarten environment on pre school children with DCD so as to provide a basis for etiological research and early intervention